A Holistic Approach to Enhance Learning Experiences for People With Hearing Disabilities in Online and Traditional Classroom Settings - Mario Perez-Enriquez; Jose Luis Lopez-Cuadrado; Israel Gonzalez-Carrasco (IEEE Access)
Digital technologies are key to how knowledge is communicated and accessed in the constantly changing educational landscape. Accessibility, which guarantees that everyone, regardless of ability, has equal opportunity to interact with educational content, is fundamental to this growth. This paper presents an integral framework for hybrid and online learning environments that provides different functionalities to address the diverse needs of students with disabilities in educational environments. The approach focuses on accessibility and user-centric design. It includes features like live transcription, synchronized recordings, and compatibility with assistive technologies to ensure equitable access to educational content and promote user engagement. The framework emphasises the live session features, AI-generated content, and the system’s ability to improve accessibility and user engagement. Moreover, integrating a Learning Management System (LMS) streamlines the teaching and learning process, offering educators and students a centralised platform for accessing essential resources. The paper also includes a detailed account of the user testing conducted to evaluate the framework’s effectiveness and usability. A comprehensive analysis of user feedback, auto-generated resource examples, and a thorough examination of various user scenarios have been undertaken to evaluate the system’s performance comprehensively. The overall perception of the proposed system achieves remarkable results, obtaining an average valuation of 4,46 out of 5.